Developing An Instruments of Financial Education Among University Students : Exploratory and Confirmatory Factor Analysis - Nuris, Dudung Ma'ruf (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to develop and validate a financial education instrument for university students. A survey method with a quantitative approach was utilized, and data analysis employed exploratory factor analysis and confirmatory factor analysis. A total of 440 respondents participated in the confirmatory analysis. This study constructed three factors, namely formal financial education, non-formal financial education, and informal financial education, which comprise 25 items. The results revealed that formal financial education presents a curriculum and learning program that is well structured and scheduled so that students can obtain recognition in the form of an official certificate from the government. Meanwhile, non-formal financial education can include financial seminars, financial training, and financial workshops organized by formal institutions. Informal financial education emphasizes the importance of the role of the family environment in understanding finance. Informal financial education emphasizes the importance of the role of the family environment in understanding finance. The implications of this study can have an impact on the readiness of universities in preparing financial education curricula that are easy to understand and practice.